Energetics of Quadruplex-Drug Recognition in Anticancer Therapy - Pagano, B.; Giancola, C. (Current Cancer Drug Targets, 2007)
Immortality of tumour cells is strictly correlated to telomerase activity. Telomerase is overexpressed in about 85% of tumour cells and maintains telomere length contributing to cell immortalisation, whereas in somatic cells telomeres progressively shorten until cell death occurs by apoptosis. Different drugs can promote telomeric G-rich overhangs which fold into quadruplex structures that inhibit telomerase activity. Detailed studies on drug-quadruplex complexes are essential to understand quadruplex recognition and address drug design. This review will discuss the energetic aspects of quadruplex-drug interactions with a particular attention to physico-chemical methodologies.
Keywords: telomeric DNA